Education of rabbit cultivators on the use of drug with the right dosage for preventing resistance - Penny Humaidah Hamid; Rini Widayati; Widagdo Sri Nugroho; Sigit Prastowo; Slamet Raharjo (Universitas Muhammadiyah Magelang, 2022)
Because of its dual purpose as livestock and pets, rabbit farming offers a number of advantages. Rabbit meat is of high quality, both in terms of taste and nutritional value. The purpose of this service activity is to provide farmers a hands-on understanding of how important it is to treat rabbit diseases at the proper dose. Veterinary care operations for 200 sick rabbits were used to educate the public. The activity continued with a dialogue about health issues in rabbit farming, which was attended by 30 cultivators. Theoretically, the dialogue is highlighted regarding the long-term consequences of not treating with the correct dose, which leads to resistance to many types of diseases to commonly used therapeutic substances. Meanwhile, practical treatment instruction focuses on treating with prudence, which includes appropriate weight estimation, the use of sterile needles, and the essential role of veterinarian considerations in treatment decisions. This community service seeks to educate rabbit farmers on the long-term effects of resistance, which can result in significant long-term losses.